mixed up with others before we even begin. - Thalmair, Franz; mumok - Museum moderner Kunst Stiftung Ludwig Wien, Wien (Köln : Verlag der Buchhandlung Walther und Franz König, 2022)
Babirye, Leilah ; Castillo Deball, Mariana ; Chişa, Anetta Mona ; Tkáčová, Lucia ; Güreş, Nilbar ; Lamas, Nicolás ; Slavs and Tatars
mixed up with others before we even begin, mumok - Museum moderner Kunst Stiftung Ludwig Wien, Wien, 26. November 2022 bis 10. April 2023
boek